¿Nueva era de proteccionismo?: El papel de los Acuerdos de Libre Comercio en América Latina - Arrieta, Gabriel (Pontificia Universidad Católica del Perú, 2017)
After the accession of Donald Trump as president of the United States, the recent protectionist trade environment is guarantee that the American trade policy could affect Latin American countries, due to the importance of United States as trading partner. These policies would not only affect Latin American countries, but also their main trading partners as China, that could respond with other protectionist policies, which could lead to the beginning of a domino effect, where the biggest loser could be Latin America. Taking into account the current international context, in this article it will be making policy recommendations on Free Trade Agreement issues aimed to reducing the possible impacts of American trade policies in Latin American countries (especially, considering the recent United States’ withdraw from the Trans-Pacific Partnership deal).

Dado el reciente ambiente comercial proteccionista suscitado tras el ingreso de Donald Trump como presidente de Estados Unidos, se presenta una gran posibilidad de que las políticas comerciales que se puedan aplicar en Estados Unidos repercutan sobre los países de América Latina, dada la importancia de Estados Unidos como socio comercial. Estas políticas no solo afectarían a los países latinoamericanos, sino también a sus principales socios comerciales (i.e. China), los cuales podrían responder con mayores políticas proteccionistas; esto podría llevar al inicio de un efecto dominó donde el gran perdedor sea América Latina. Por tal motivo, tomando en cuenta el actual contexto internacional, se buscará, en el presente artículo, realizar recomendaciones de políticas en temas de Acuerdos de Libre Comercio, orientadas a reducir los posibles impactos de las políticas comerciales norteamericanas en la región de América Latina (especialmente considerando la reciente salida del Trans-Pacific Partnership).
New Protectionism? : The role of Free Trade Agreements in Latin America
Keywords: Latin America; Free Trade Agreements; United States; International Trade; Donald Trump; América Latina; Acuerdos de Libre Comercio; Estados Unidos; Comercio Internacional; Donald Trump; https://purl.org/pe-repo/ocde/ford#5.06.00